Innovation and its effects on compliance with Sustainable Development Goals and competitiveness in European Union countries - Álvarez Risco, Aldo Rodrigo (2023)
Innovation in a country should have an impact on different indicators of a country. Thus, it can be expected to have an impact on the fulfillment of the Sustainable Development Goals (SDG) and, finally, on the country's competitiveness. This study analyzes the effect that innovation, in its human and financial resources components, has on the fulfillment of the SDGs and, likewise, how this fulfillment has an effect on the competitiveness of the countries of the European Union. The information used for innovation was reported on the European Commission's website; in the case of the SDGs, information from the SDG Index 2022 report was used. Finally, information on competitiveness was obtained from the World Competitiveness Ranking. The information from the 25 countries that had results in the sources was analyzed. The data collected were analyzed using the partial least squares structural equation modeling technique. It was evidenced that innovation based on human resources and finance have a positive and significant effect on SDG compliance; furthermore, it is shown that SDG compliance has a positive and significant effect on the competitiveness of European Union countries. These results show the great importance of monitoring global indicators to generate better positioning and alternatives for development and welfare for countries.